Comparison Between the Image Information of T2WI FLAIR Sequences and TSE T2WI Axial Slice Brain MRI Examination with Cases of Intracranial Tumors - Annisa, Aulia; Mesra, Yuni; Hasan, Dody Pratama (Journal of Social Work and Science Education, 2023)
This study aims to determine the most optimal results of image information generated from the two sequences, especially for diagnosing intracranial tumors. This type of research is an experiment. The research was conducted with an MRI 3 Tesla in the Radiology Installation. The data is in the form of 20 MRI Brain images from the T2WI TSE and T2WI FLAIR sequences with cases of intracranial tumors. Image evaluation from the qualitative aspect was obtained from respondents’ assessments which were analyzed by Wilcoxon different tests and cross-tabulation. While the quantitative assessment is obtained from the measurement of the Signal Noise Ratio (SNR) and analyzed by the Paired T-Test. Based on the results of the study, Ho was rejected and Ha was accepted, which means that there is a difference in image information between the T2WI TSE sequence and the T2WI FLAIR sequence on the axial section of the MRI Brain examination in cases of intracranial tumors with a p-value = 0.034 (p <0.05). The T2WI TSE sequence can show good intensity and tumor boundaries, while the FLAIR T2WI sequence can show edema around the tumor well, while white matter and gray matter lesion assessments show no significant difference between the two sequences. The results of the SNR measurements showed that the Signal Noise Ratio (SNR) value of the T2WI TSE sequence was higher than that of the FLAIR T2WI sequence.